Anticoagulant in Acute Ischemic Stroke with Atrial Fibrillation: A Narrative Review - Sayeed, S K Jakaria Been; Moniruzzaman, Md; Rahman, Md Mujibur (Journal of Medicine, 2024)
Embolic stroke due to atrial fibrillation is often underdiagnosed and has high morbidity and mortality among ischemic stroke. So it is of paramount importance to start anticoagulants as early as possible to prevent further ischemic stroke. However, early initiation of anticoagulants has created much debate, major & minor bleeding related to it are a major concern, and resumption of anticoagulants after intracranial hemorrhage is still a gray zone. Here, we described a narrative review to shed some light on the major concerns such as the optimal time to start an anticoagulant, the best agent to administer, the resumption of anticoagulant after a hemorrhagic stroke, and anticoagulant therapy in chronic rheumatic heart disease (CRHD) based on the recently published article. J MEDICINE 2024; 25: 155-158